2020
DOI: 10.1001/jamanetworkopen.2020.19046
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Cord Blood Vitamin D and Preeclampsia With Offspring Blood Pressure in Childhood and Adolescence

Abstract: Key Points Question What is the association of in utero exposure to preeclampsia with blood pressure in childhood and adolescence, and does the association differ by cord blood vitamin D levels? Findings In this cohort study of 754 mother-child pairs with 6669 blood pressure observations, maternal preeclampsia was associated with higher offspring systolic blood pressure from early childhood to adolescence. This association, however, was attenuated among chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
(109 reference statements)
0
13
0
1
Order By: Relevance
“…In adults, some studies suggested that Se and Mn may have protective effects against hypertension and CVD, although there is also evidence of possible adverse effects, nonlinear relationships, or null effects of these elements on BP and CVD (Bulka et al 2019;Laclaustra et al 2009; Lee and Kim 2011; Mordukhovich et al 2012;Nawrot et al 2007;Wu et al 2017). In pregnant women, we reported in the Boston Birth Cohort (Liu et al 2019) and in Project Viva (Liu et al 2020) that higher maternal Mn levels were prospectively associated with lower risk of preeclampsia, a pregnancy complication characterized by high BP and a known risk factor for child high BP (Zhang et al 2020b). It is unclear how in utero exposure to Se and Mn is associated with BP in children.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In adults, some studies suggested that Se and Mn may have protective effects against hypertension and CVD, although there is also evidence of possible adverse effects, nonlinear relationships, or null effects of these elements on BP and CVD (Bulka et al 2019;Laclaustra et al 2009; Lee and Kim 2011; Mordukhovich et al 2012;Nawrot et al 2007;Wu et al 2017). In pregnant women, we reported in the Boston Birth Cohort (Liu et al 2019) and in Project Viva (Liu et al 2020) that higher maternal Mn levels were prospectively associated with lower risk of preeclampsia, a pregnancy complication characterized by high BP and a known risk factor for child high BP (Zhang et al 2020b). It is unclear how in utero exposure to Se and Mn is associated with BP in children.…”
Section: Introductionmentioning
confidence: 82%
“…In this Guideline, BP percentiles were calculated using new normative BP tables based on SBP and diastolic BP (DBP) readings arranged by age, sex, and height from ∼ 50,000 normal-weight children and adolescents (Flynn et al 2017). We used SBP as the primary outcome and DBP as the secondary outcome, because SBP is more strongly associated with hypertension and CVD in adulthood (Chen and Wang 2008;Sun et al 2007); this approach is consistent with our previous studies in the Boston Birth Cohort (Zhang et al 2018(Zhang et al , 2020b.…”
Section: Child Bpmentioning
confidence: 92%
“…However, a randomized trial showed that vitamin D treatment did not affect the blood pressure of the patients compared to placebo [19]. A review [20] and a meta-analysis [21] revealed that vitamin D supplementation did not reduce blood pressure. These conclusions may be that the study population happens to be a low-magnesium population.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension in this population is the prominent risk factor for pregnancy-related hypertension, such as preeclampsia and eclampsia, which are the leading cause of maternal and fetal mortality. It is also associated with an increased risk of childhood adverse health outcomes in the long term, including asthma [ 5 ], elevated blood pressure [ 6 ], as well as some rare childhood cancers [ 7 ]. Furthermore, postmenopausal women’s unique physiological conditions can affect BP in several hormonal ways [ 8 ], which also provides a unique risk for hypertension-related cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%